Therapeutic effect of Internal iliac artery ligation and uterine artery ligation techniques for bleeding control in placenta accreta spectrum patients: A meta-analysis of 795 patients - Nabhan, Ayman Essa; AbdelQadir, Yossef Hassan; Abdelghafar, Yomna Ali; Kashbour, Muataz Omar; Salem, Nour; Abdelkhalek, Abdelrahman Naeim; Nourelden, Anas Zakarya; Eshag, Mona Muhe Eldeen; Shah, Jaffer (Frontiers in Surgery, 2022)
Placenta accreta spectrum (PAS) can cause complications like hysterectomy or death due to massive pelvic bleeding. We aim to evaluate the efficacy of two different arterial ligation techniques in controlling postpartum haemorrhage and minimizing bleeding complications. We searched six databases. 11 studies were finally included into our review and analysis. We graded their quality using the Cochrane tool for randomized trials and the NIH tool for retrospective studies. Our analysis showed that internal iliac artery ligation has no significant effect on bleeding control (MD = - 248.60 [-1045.55, 548.35] P = 0.54), while uterine artery ligation significantly reduced the amount of blood loss and preserved the uterus (MD = -260.75, 95% CI [-333.64, -187.86], P < 0.00001). Uterine artery ligation also minimized the need for blood transfusion. Bleeding was best controlled by combining both uterine artery ligation with uterine tamponade (MD = 1694.06 [1675.34, 1712.78], P < 0.00001). This combination also showed a significant decrease in hysterectomy compared to the uterine artery ligation technique alone. Bilateral uterine artery ligation in women with placenta accreta spectrum can effectively reduce the amount of bleeding and the risk of complications. The best bleeding control tested is a combination of both, uterine artery ligation and cervical tamponade. These techniques may offer an easy and applicable way to preserve fertility in PAS patients. Larger randomized trials are needed to define the best technique.